Thermodynamic analysis of water vapor adsorption onto freeze-dried ora-pro-nobis (Pereskia aculeata Miller) mucilage - Bruna de Souza Nascimento; Giovanni Aleixo Batista; Vinicius Tessinari Pravato; Gabriel Pedroso de Lima Alexandre; Lizzy Ayra Alcântara Veríssimo; Jaime Vilela de Resende (The Journal of Engineering and Exact Sciences)
The mucilage of Pereskia aculeata Miller is a hydrocolloid with the potential to be used as a food additive. Thus, data on its physical, chemical and microbiological stability are necessary to evaluate the storage stability of the product. This study aimed to determine the thermodynamic properties of water vapor adsorption onto freeze-dried ora-pro-nobis mucilage (OPNM) and to interpret the mechanisms that govern water adsorption onto powder particles through the study of enthalpy-entropy compensation. In addition, OPNM was characterized in terms of moisture, ash, ether extract, protein, fiber and carbohydrates beyond the functional chemical groups by Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). Thermodynamic analysis showed that water adsorption onto OPNM powder was characterized as a spontaneous process with strong attractive forces in the water and OPNM mixture. The water sorption mechanism for OPNM at the studied adsorption range was regulated by energy interactions related to the chemical composition of the product.